2020
DOI: 10.1186/s12913-020-05590-y
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: General practitioners’ and out-of-hours doctors’ role as gatekeeper in emergency admissions to somatic hospitals in Norway: registry-based observational study

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Sex, ethnicity, and education level are other variables that may influence health, the use of health services, and mortality. Since there are geographical differences in the use of hospitals and OOH services, 23,24 the analysis also adjusted for a rural-urban variable (centrality). It is possible that healthy patients with few visits may have long continuity without the benefit of being well known by their RGP.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Sex, ethnicity, and education level are other variables that may influence health, the use of health services, and mortality. Since there are geographical differences in the use of hospitals and OOH services, 23,24 the analysis also adjusted for a rural-urban variable (centrality). It is possible that healthy patients with few visits may have long continuity without the benefit of being well known by their RGP.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The primary care contact prior to admission might be random, and not related to the admission. In a previous study we found a distinct accumulation of GP and OOH contacts within 24 h before acute hospital admission [ 9 , 10 ]. This indicates that the assumption that a contact within 24 h before an admission is the referral contact, is valid.…”
Section: Discussionmentioning
confidence: 99%
“…For referrals with abdominal and chest pain symptoms, the most frequent ICD-10 discharge diagnoses were the corresponding symptom-based diagnoses abdominal and pelvic pain (R10) and pain in throat and chest (R07). Our previous study showed that these discharge diagnoses were the overall second and third most frequent discharge diagnoses after acute admissions to hospital, irrespective of referral agent [ 9 , 10 ]. Such extensive use of symptom diagnoses both in referrals and discharges could serve as a reminder of the diagnostic challenges in both primary care and in hospitals but might as well be an indication of defensive medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations